1981
DOI: 10.1128/iai.33.2.546-554.1981
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the intracellular stage of Trypanosoma cruzi and its interaction with mouse macrophages in vitro

Abstract: Interaction between Trypanosoma cruzi spheromastigotes (amastigotes) and mouse macrophages was studied. The spheromastigotes, isolated from the spleens of infected mice, were incorporated and digested by the macrophages. By use of horseradish peroxidase labeling of the macrophage lysosomes we showed that fusion of lysosomes with phagocytic vacuoles containing T. cruzi occurred. Parasites showing alterations indicative of digestion were seen inside the phagocytic vacuoles. Our results suggest that intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Carvalho et al . (14) and Gutteridge et al . (15) showed that amastigotes isolated from the spleen or muscle of mice were not infective to mouse peritoneal macrophages or infective when injected into animals.…”
Section: Discussionmentioning
confidence: 93%
“…Carvalho et al . (14) and Gutteridge et al . (15) showed that amastigotes isolated from the spleen or muscle of mice were not infective to mouse peritoneal macrophages or infective when injected into animals.…”
Section: Discussionmentioning
confidence: 93%
“…Andrews et al[2,31 showed that Ssp-4 is released from intracellular and extracellular amastigotes. We and others have shown that extracellular amastigotes can invade professional [ 5 ,7,20,22, 271 as well as nonprofessional phagocytes [20, 2 5 , 291. Since amastigotes lack several o f the components thought to be involved in trypomastigotes invasion like penetrin [ 161, trans-sialidase and sialic acid acceptors[33]…”
mentioning
confidence: 99%
“…For the 120 h period of the observations, the increment over the initial number of parasites was in the order Y > Tulahuen > CL (38.7 > 16. 3 > 14.7 times in the presence of 5% CO,; 30.7 > 9.7 > 3.1, no CO, present). In the preparative phase, 2 g of Y amastigotes were readily obtained from two liters of culture.…”
Section: Isolation Of Amastigotes From Infected Cell Culturesmentioning
confidence: 87%
“…P immunology of Trypanosoma cruzi has been hampered by difficulties in obtaining sufficient purified tissue stages of the parasite (known as amastigotes, spheromastigotes or micromastigotes). The common source of amastigotes has been infected animal tissue; the methods have been rather laborious and time-consuming, and the yields very low ( I , 3,5,7). The importance of improving procedures to produce large quantities of T. cruzi amastigotes is emphasized by these being the forms multiplying intracellularly in mammalian hosts and accounting for production of new trypomastigotes that disseminate the infection in the body.…”
mentioning
confidence: 99%